A Pattern for Eco-park design in Beshghardash landscape - Ghorbanzadeh, Mojgan; Taghvaei, Seyed Hasan (Ciência e Natura, 2015)
Nowadays, attention to strengthen environmental problems, effected from increasing population and process of development in countries, one of the major concern of designers is recognition of the suitable conditions of natural environment, and promotion of the environmental quality. This case with focus to present capabilities and uses of biodiversity and domestic is applied. Eco-park is one of the capabilities which have been designed to the following objectives: Protection of environment and environmental technology progress, Promenade and demonstrate, Learning information for public and Displaying unification between nature and human and their mutual relationship for promotion the comprehension of environment.This paper is about investigation and recognition of capabilities, for creating the suitable situation to change as regional Eco-park. The Case study is named "Beshghardash" that is located in 5th Kilometers Bodjnourd ( center of northern Khorasan province ). This region has approximately 380 hectares area and located in cold and dry climate , which is one of the attractive tourism centers in this region . This study is based on four principles as the following: Protection principle, Development principle, Principle of responsibility to public welfare in present and future, Adapting with situations principle. Finally pattern of designing the Beshghardash Eco-park following the objectives which are in sustainable environment and can say that Beshghardash Eco-park is a natural environment , which moreover to verify to environmental values can answer the sustainable development , like improving the humans life quality.